2008
DOI: 10.1097/phm.0b013e318164a99a
|View full text |Cite
|
Sign up to set email alerts
|

Center-of-Pressure Displacement During Postural Changes in Relation to Pressure Ulcers in Spinal Cord-Injured Patients

Abstract: The results of this study suggest that impaired dynamic sitting stability is associated with pressure ulcer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…As with the studies on bed positioning, there was significant heterogeneity of methods and outcomes of seated positioning and pressure relief maneuvers, precluding aggregation of study results. Study designs were primarily case series [51‐57], cohort [44,58‐63], or cross‐sectional [64‐72]. There was one N‐of‐1 study and one RCT [73,64].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As with the studies on bed positioning, there was significant heterogeneity of methods and outcomes of seated positioning and pressure relief maneuvers, precluding aggregation of study results. Study designs were primarily case series [51‐57], cohort [44,58‐63], or cross‐sectional [64‐72]. There was one N‐of‐1 study and one RCT [73,64].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (19) were conducted in a laboratory setting [44,51‐63,68‐72]. Six studies [64‐66,73] were conducted in the clinic, and two of these studies [67,74] were with community‐dwelling subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karatas et al [18] found that the COP displacements for 16 SCI participants were significantly smaller in all directions (forward, backward, left, and right) than the measurements for 18 able-bodied subjects. The change in COP was expected to be smaller for the SCI cohort due to physiological differences in SCI individuals.…”
Section: Activity To Encourage Pressure Relieving Movementsmentioning
confidence: 99%
“…Karatas et al [18] found that SCI participants, with a history of pressure ulcers, had a smaller COP displacement than SCI participants with no history of pressure ulcers, which could not be explained by level of injury [18]. Therefore, it is possible that the ability to perform larger postural movements allows for more pressure relief and thus the group of SCI participants who could perform these movements had healthier tissue; however, as other interfacial pressures (such as peak pressure index, total contact area, and dispersion index) were not reported it is unwise to make a judgement.…”
Section: Activity To Encourage Pressure Relieving Movementsmentioning
confidence: 99%